The use of Pomegranate Juice for Counteract Lipid Peroxidation that Naturally occurred During Liquid Storage of Roosters’ Semen - Al-Daraji, Hazim J. (Pharmacognosy Communications)
Materials and Methods: In an attempt to find a suitable in vitro storage method for roosters’ semen, an experiment was conducted to study the influence of inclusion pomegranate juice (PJ) into semen diluent on semen quality during liquid storage for up to 36 h. A total of 60 White Leghorn roosters, 40 weeks of age, randomly divided into 6 treatment groups (10 males each) were used in this study. Treatment groups were as follows: T1 = fresh semen, T2 = semen diluted 1:2 with Al-Daraji 2 diluent (AD2D) alone, T3 – T6 = semen diluted 1:2 with AD2D supplemented with 2 ml, 4 ml, 6 ml or 8 ml of PJ / 100 ml of diluent, respectively. Semen samples were assessed after in vitro storage at 4 – 6˚C for 12 h, 24 h or 36 h as regards mass motility, individual motility and percentages of dead spermatozoa, abnormal spermatozoa and acrosomal abnormalities. Results: Results revealed that supplementing the diluent of roosters semen with PJ (T3, T4, T5 and T6) and then storing it for different storage periods (12 h, 24 h or 36 h) resulted in significant (p < 0.05) improvement in spermatozoa motility, viability, morphology and acrosomal integrity in comparison with the control group (T1). Moreover, T5 and T6 surpassed other treatments with respect to these semen characteristics, while there were no significant differences between T2, T3 and T4 concerning all semen traits included in this study. Conclusion: In conclusion, the substitution of AD2D diluent composition with PJ significantly improves the quality of roosters semen that is in vitro stored for up to 36 h. Furthermore, the positive effect of PJ observed in this study may be due to enhanced sperm resistance to lipid peroxidation that naturally occurred during in vitro storage of avian semen.
Keywords: Pomegranate juice; lipid peroxidation; liquid storage; roosters’ semen